2020
DOI: 10.1039/d0nr03766d
|View full text |Cite
|
Sign up to set email alerts
|

Molecular physics of jumping nanodroplets

Abstract: Next-generation processor-chip cooling devices and self-cleaning surfaces can be enhanced by a passive process that require little to no electrical input, through coalescence-induced nanodroplet jumping. Here, we describe the crucial...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…However, there is no consensus on how small a coalesced droplet can detach from a surface [24][25][26][27][28][29], which is associated with the Ohnesorge number 𝑂ℎ = 𝜇/√𝜌𝜎𝑅 that characterizing the relative importance of viscous versus capillary-inertial effects, where 𝜇 , 𝜌 , 𝜎 and 𝑅 are the liquid dynamics viscosity, the liquid density, the surface tension and the radius of droplet, respectively. While earlier researches once suggested that jumping events will not occur below a critical size of 𝐷 c ~ 10 μm (in large 𝑂ℎ range) [11,24,30], the minimum jumping-droplet radius 𝑅 c has exceeded the submicron scale in recent experimental observations [25], even some numerical evidences indicate that nanoscale coalescenceinduced jumping should be possible [28,[31][32][33][34]. It was revealed that 𝑅 c is also dependent on the surface topology and the finer structure would enable smaller jumping droplets [27], so some intriguing questions arise accordingly, how to predict the critical departure size for a nanostructured surface and whether the self-removal can be achieved for the naturally grown (condensed) nanodroplets?…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, there is no consensus on how small a coalesced droplet can detach from a surface [24][25][26][27][28][29], which is associated with the Ohnesorge number 𝑂ℎ = 𝜇/√𝜌𝜎𝑅 that characterizing the relative importance of viscous versus capillary-inertial effects, where 𝜇 , 𝜌 , 𝜎 and 𝑅 are the liquid dynamics viscosity, the liquid density, the surface tension and the radius of droplet, respectively. While earlier researches once suggested that jumping events will not occur below a critical size of 𝐷 c ~ 10 μm (in large 𝑂ℎ range) [11,24,30], the minimum jumping-droplet radius 𝑅 c has exceeded the submicron scale in recent experimental observations [25], even some numerical evidences indicate that nanoscale coalescenceinduced jumping should be possible [28,[31][32][33][34]. It was revealed that 𝑅 c is also dependent on the surface topology and the finer structure would enable smaller jumping droplets [27], so some intriguing questions arise accordingly, how to predict the critical departure size for a nanostructured surface and whether the self-removal can be achieved for the naturally grown (condensed) nanodroplets?…”
Section: Introductionmentioning
confidence: 95%
“…It was revealed that 𝑅 c is also dependent on the surface topology and the finer structure would enable smaller jumping droplets [27], so some intriguing questions arise accordingly, how to predict the critical departure size for a nanostructured surface and whether the self-removal can be achieved for the naturally grown (condensed) nanodroplets? Unfortunately, to date, these issues have not been exactly solved despite many efforts to investigate the nanometric jumping droplets [28,[34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…ACS SCE will encourage rapid publication of emerging directions and in-depth investigations of phenomena and applications in the area. Parallel to the developments in NBs, we are aware of the emerging science in the area of droplets, where accelerated reactions, , new phenomena, , and synthesis and transformation of nanomaterials , are attracting attention, which can also contribute to sustainability by controlling fluids at smaller length scales.…”
Section: Holey Liquids and The “Nanophase”mentioning
confidence: 99%
“…Unlike traditional computational fluid dynamics simulations, the MD method can directly explore the nanoscopic origins, elucidate phenomena from a molecular perspective, and provide a fundamental understanding that is not accessible by experiments; thus, it has been widely used to investigate various interfacial phenomena, such as droplet wetting, , impact, coalescence, , and evaporation, , as well as liquid boiling and vapor condensation. , In this paper, nonequilibrium molecular dynamics simulations were performed to investigate the nanoscale thin-film boiling process. Aiming at understanding the initial bubble behaviors and the heat and mass transfer performance, this work was conducted and illustrated around the following objectives: (1) capturing the triple-phase interface to record the lifetime of nanobubbles, (2) visualizing the internal fluid flow and thermal characteristics, (3) studying the effects of surface physicochemical properties on boiling performance, and (4) revealing the essential regulation mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike traditional computational fluid dynamics simulations, the MD method can directly explore the nanoscopic origins, elucidate phenomena from a molecular perspective, and provide a fundamental understanding that is not accessible by experiments; thus, it has been widely used to investigate various interfacial phenomena, such as droplet wetting, 32,33 impact, 34−37 coalescence, 38,39 and evaporation, 40,41 as well as liquid boiling 42−47 and vapor condensation. 32,48−52 In this paper, nonequilibrium molecular dynamics simulations were performed to investigate the nanoscale thin-film boiling process.…”
Section: Introductionmentioning
confidence: 99%